A Perspective of Geomorphology for Landslide Susceptibility and its Applied in the Taji Village-Malang Regency as Vulcanic Area - Masruroh, Heni; Bachri, Syamsul; Purwanto, Purwanto; Mutia, Tuti (International Journal of Disaster Management, 2024)
Landslides are Indonesia's second-largest disaster during 2020-2022. Many researchers have conducted research related to landslides, i.e., landslide susceptibility with statistical, heuristic, geomorphological approaches and landslide disaster risk. The geomorphological approach is one approach in the study of landslides that can represent morphology, morphostructure, morphochronology, and morphoarrangements. This research aims to explain landslide hazard mapping using a geomorphological approach, evidenced by a case study in the Gede watershed as one of the watersheds in Taji Village. The method used in this research is Geomorphology approach using a systematic literature review. Furthermore, landslide susceptibility analysis has been carried out using a geomorphological approach with topographic position analysis a case study in Taji Village. The results showed that landslides can be more specifically identified through morphology, surface material resulting from morphochronological and morphological processes, and existing and dormant geomorphological processes. These four aspects can be used as the key to the identification of landslide hazards. Based on the geomorphological approach, as much as 52.13% is very high vulnerability located on the upper slope morphology, 25.45% high vulnerability on the middle slope, 10.16% medium vulnerability on the lower slope, and 12.26% low vulnerability on the slope morphology foot.